Making Space for Failure in the Scholarship of Teaching and Learning: A Blueprint - Nancy L. Chick; Laura Cruz; Jennifer C. Friberg; Hillary H. Steiner (Teaching & Learning Inquiry: The ISSOTL Journal, 2023)
In this essay, we offer a typology of failure in the scholarship of teaching and learning (SoTL) to serve as the foundation for a new line of inquiry to be featured in this new section of Teaching & Learning Inquiry — SoTL in Process. Through the typology, we advocate for making space to talk about failure and its many forms in SoTL.